2004
DOI: 10.1142/s0217732304014689
|View full text |Cite
|
Sign up to set email alerts
|

LIMITS ON THE DIPOLE MOMENTS OF THE τ-LEPTON VIA THE PROCESS e+e-→τ+τ-γ IN A LEFT–RIGHT SYMMETRIC MODEL

Abstract: Limits on the anomalous magnetic moment and the electric dipole moment of the τ lepton are calculated through the reaction e + e − → τ + τ − γ at the Z 1 -pole and in the framework of a left-right symmetric model. The results are based on the recent data reported by the L3 Collaboration at CERN LEP.Due to the stringent limit of the model mixing angle φ, the effect of this angle on the dipole moments is quite small.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…2 of the Ref. [53]. Our results for the dependence of the differential cross section on the photon energy versus the cosine of the opening angle between the photon and the beam direction (θ γ ) are presented in Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…2 of the Ref. [53]. Our results for the dependence of the differential cross section on the photon energy versus the cosine of the opening angle between the photon and the beam direction (θ γ ) are presented in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…In a previous paper [53] we estimated bounds on the anomalous magnetic moment and the electric dipole moment of the tau through the process e + e − → τ + τ − γ in the context of a LRSM at the Z 1 pole. We found that these bound were almost independent of the mixing angle φ of the model.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there has been extensive theoretical work done in BSM models that contributes to dipole moments of charged leptons: CP-violation BSM [14], extra dimensions [15], seesaw model [16], version III of the two-higgs-doublet model [17], noncommutative geometry [18], nonuniversal extra dimensions [19], left-right symmetric model [20], E 6 superstring models [21], simplest little Higgs model [22], and 331 model [23]. There are also bounds independent of the model such as γp collisions [24], e − γ scattering [25], and γγ collisions [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Since CP violating dipole moment highly suppressed in the SM (induces with three loop level [9]), any measurement at colliders of the electric dipole moment of the tau lepton gives hints about the new physics beyond the SM. The CP violation may come from new physics theories in lepton sector such as leptoquark [10,11], SUSY [12], left-right symmetric [13,14] and Higgs models [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%